Strategi Guru dalam Program Pembinaan Akhlakul Karimah Siswa Kelas 3 (Luqman) di SDIT Al-Irsyad Al-Islamiyyah Karawang - Aprilia Esa Gustiana; Achmad Junaedi Sitika; Debibik Nabilatul Fauziah (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2022)
SDIT Al-Irsyad Al-Islamiyyah Karawang is one of the da'wah institutions that has one mission, namely instilling Islamic faith, sholilah worship and morality based on the Qur'an and Sunnah. With one of its goals to form students who are faithful and devoted, intelligent, and have noble character. Has a variety of excellent programs in which there is a moral development of students. This study aims to identify and describe the student morality development program as the implementation of character education at SDIT Al-Irsyad Al-Islamiyyah Karawang. Using descriptive qualitative research methods by conducting direct observations and interviews with classroom teachers. The results showed that the student morality development program at SDIT Al-Irsyad Al-Islamiyyah Karawang includes various activities that provide feedback as a form of habituation to noble actions in daily activities. The strategy that the teacher uses in implementing moral development is through two approaches, namely direct education and indirect education. The supporting factor for the running of the student's morality development activities is the collaboration between the student's guardian and the homeroom teacher. The inhibiting factor is due to the lack of awareness or desire of students in participating in these coaching activities. To overcome the obstacles that occur in the process of fostering student morality, teachers often give rewards in the form of stars to students.